ANALISIS KUALITAS AIR IRIGASI UNTUK BUDIDAYA PADI DI KECAMATAN BACHOK, KELANTAN, MALAYSIA - Arjun Sanjaya; Wan Arfiani Barus; S Mohamad Shahid (Fakultas Pertanian, Universitas Janabadra, 2024)
Irrigation water quality analysis was conducted in Bachok District, Kemubu Agriculture Development Authority (KADA) Malaysia in September 2023. The irrigation water quality analysis was conducted by measuring several physical and chemical water qualities at eight sampling points. The sampling locations were primary irrigation canals used to supply water to rice fields. The parameters measured include temperature, pH, Conductivity, Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), Ammoniacal Nitrogen (AN), Ca, Na and Mg. This study aims to determine the quality of irrigation water for rice fields in Bachok District, Kemubu Agriculture Development Authority (KADA) Malaysia using Water Quality Index (WQI) and Sodium Adsorption Ratio (SAR). The results showed that the Water Quality Index at all sampling points ranged from 71.87 to 92.14 with an average of 84.33 which indicates that irrigation water falls into the category of very good and sufficient water. Meanwhile, the SAR value varied between 2.42-5.42, which means that all irrigation water samples are in the very good category and are suitable for irrigation purposes and better development of rice cultivation policies in KADA. Keywords: irrigation water, water quality index (WQI), Sodium Adsorption Ratio (SAR) INTISARIAnalisis kualitas air irigasi dilakukan di Kecamatan Bachok, Kemubu Agriculture Development Authority (KADA) Malaysia pada September 2023. Analisis kualitas air irigasi dilakukan dengan mengukur beberapa kualitas fisik dan kimia air di delapan titik pengambilan sampel. Lokasi pengambilan sampel adalah saluran irigasi primer yang digunakan untuk menyuplai air ke sawah. Parameter yang diukur antara lain adalah suhu, pH, Conductivity, Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), Ammoniacal Nitrogen (AN), Ca, Na and Mg. Penelitian ini bertujuan untuk mengetahui kualitas air irigasi untuk persawahan di Kecamatan Bachok, Kemubu Agriculture Development Authority (KADA) Malaysia dengan menggunakan Water Quality Indeks (WQI) dan Sodium Adsorption Ratio (SAR). Hasil penelitian menunjukkan Indeks Kualitas Air di seluruh titik pengambilan sampel berkisar antara 71,87 hingga 92,14 dengan rata-rata 84,33 yang menunjukkan bahwa air irigasi masuk dalam kategori air sangat baik dan cukup. Sementara itu nilai SAR bervariasi berkisar antara 1,98 - 5,42 yang berarti seluruh sampel air irigasi termasuk dalam kategori sangat bagus dan layak untuk keperluan irigasi dan pengembangan kebijakan budidaya padi di KADA dengan lebih baik. Kata kunci: air irigasi, indeks kualitas air (WQI), Rasio Adsorpsi Natrium (SAR)